Offspring provisioning by extra‐pair males in blue tits. (16th March 2021) - Santema, Peter; Kempenaers, Bart
Abstract : Most birds are socially monogamous with both parents providing offspring care, but sometimes individuals are observed to provision at a nest that is not their own. One possible explanation for this behaviour is that it is a fitness maximising strategy by males who have copulated with the female and hence potentially sired extra‐pair offspring in the focal nest. Over a period of 8 years and among a total of 854 nests, we observed 12 blue tits Cyanistes caeruleus that provisioned at a nest that was not their own. In all cases, the provisioning individual was a male who had no nestlings of its own, either because its breeding attempt had failed (n = 5), because it was a non‐breeder (n = 6) or because the eggs in its own nest had not hatched yet (n = 1). Only two out of the 12 males had sired offspring in the nest where they helped, but most others had had interactions with the female during her presumed fertile period or were close neighbours, and hence may have performed extra‐pair copulations that did not result in fertilisations. In 10 out of the 12 cases, the resident male was not present anymore, either because it had disappeared (n = 7) or because it was socially polygynous and provided care at its other, primary nest (n = 3). Our findings suggest that females can benefit from extra‐pair copulations by obtaining help in raising their brood when they do not receive help from their social mate. Extra‐pair copulations could thus function as an 'insurance' strategy with a relatively small cost.